Pemanfaatan Tandan Kosong Kelapa Sawit sebagai Pestisida Nabati untuk Meningkatkan Potensi Ekonomi Lokal di Desa Lae Riman - Angkat, Ramisah; Hutabarat, Malfajri; Hajar, Siti; Riadhi, Zukhri; Zakia, Zahara; Hilma, Tahta; Ramayuda, M. Agung; Renaldi, Renaldi; Sampena, Iwan Doa (Medan Resource Center, 2024)
Utilization of oil palm empty fruit bunches empty palm bunches as a vegetable pesticide in Lae Riman Village aims to increase the potential of the local economy and reduce the negative environmental impact due to palm oil plantation waste. This activity was carried out as part of Teuku Umar University's Regular Community Service Program (KKN), with a direct approach and socialization to the community. direct approach and socialization to the community. Utilization of oil palm empty fruit bunches empty palm fruit bunches is expected to be able to replace the use of chemical pesticides that are expensive and risky to health. which are expensive and risky to health. In addition to improving the welfare of farmers through reduced production costs, this program also opens up new business opportunities based on organic waste management. opportunities based on organic waste management. The results of this activity showed an increase in community awareness in utilizing the potential of potential in a more economical and environmentally friendly way. This program is also expected to can be a solution that can be practiced for other villages that have similar conditions in sustainable waste management. similar conditions in an effort to manage waste sustainably.